PENGARUH ENTREPRENEURIAL LEADERSHIP, ENTREPRENEURIAL ORIENTATION, DAN INNOVATION CAPACITY TERHADAP COMPETITIVE ADVANTAGE PADA UMKM BATIK UDAR WELINGAN - Putri Oktovita Sari (UNIVERSITAS PGRI MADIUN, 2024)
This research aims to determine the influence of Entrepreneurial Leadership, Entrepreneurial Orientation, and Innovation Capacity on Competitive Advantage in the Small and Medium-sized Enterprises (UMKM) of Batik Udar Welingan in Kenongomulyo Village, Magetan. The sample in this study consisted of 55 individuals who are involved in the Batik Udar Welingan UMKM in Kenongomulyo Village. The research instrument used a questionnaire with 22 statements. Data analysis in this study employed multiple regression analysis using the SPSS application. The results of this research indicate that the Entrepreneurial Leadership variable has a positive and significant effect on Competitive Advantage in Batik Udar Welingan UMKM in Kenongomulyo Magetan. The Entrepreneurial Orientation variable has a positive and significant effect on Competitive Advantage in Batik Udar Welingan UMKM in Kenongomulyo Magetan. The Innovation Capacity variable has a positive and significant effect on Competitive Advantage in Batik Udar Welingan UMKM in Kenongomulyo Magetan.